Efektivitas Organisasi Usaha Mikro, Kecil, dan Menengah (UMKM): Tinjauan Sistematis Literatur mengenai Peran Orientasi Strategis - Bagus Hanafi Putra Ramadi; Sri Utami Nurhasanah (STIE KASIH BANGSA, 2026)
Organizational effectiveness has become a critical issue for Micro, Small, and Medium Enterprises (MSMEs) in responding to increasingly dynamic, competitive, and technology driven business environments. This study aims to systematically review the existing literature on the role of strategic orientation, organizational learning capability, and innovation in enhancing MSME organizational effectiveness. A qualitative research approach employing the Systematic Literature Review (SLR) method was adopted following the PRISMA 2020 guidelines. Relevant articles were retrieved from reputable international databases, with publications ranging from 2019 to 2025. The findings reveal that strategic orientation significantly influences organizational effectiveness through organizational learning capability and innovation as complementary mediating mechanisms. Organizations characterized by strong learning capability are more capable of generating sustainable innovation, thereby improving adaptability, competitiveness, and long term organizational effectiveness. This review contributes to the strategic management literature by integrating the Knowledge-Based View and Stakeholder Theory, while offering practical insights for policymakers and MSME managers in designing sustainable organizational development strategies.